Food security and GMOs - Schlett, András; Beke, Judit (Studia Mundi – Economica, 2015)
This study deals with potential food security impacts of GM technology. GMOs are a debated issue in the current Transatlantic Trade and Investment Partnership (TTIP) trade negotiations, lending particular significance to our topic. Patents have been issued on gene sequences that allow biotech giants the exclusive right to profit from these varieties. To protect the specific genes, in addition to the desired properties seed infertility is also encoded. As a consequence, farmers who are no longer able to produce their own seeds become completely defenceless against multinational producers. In this way the supply of staple foods, like food grains, will be monopolized by transatlantic companies, giving them control over the markets, making self-sufficiency of nations and local producers impossible.